Análise do processo regulatório ambiental na implantação de pequenas centrais hidrelétricas no estado de Minas Gerais - Mateus Romão Oliveira (2020)
Environmental licensing is one of the main instruments of the National Environment Policy (PNMA). It is applied to enterprises which are potentially polluting and degrading the environment, such as Small Hydropower Plants (SHP), since its construction causes significant environmental and social damage to the region where it is intended to deploy and operate them. Given the current interest in renewable energy sources for electricity generation, and in order to contribute to mitigating the emission of greenhouse gases, the objective of this study was to investigate the effectiveness of the environmental licensing of SHPs, considering the technological profile, the constructive aspects, the socioenvironmental impacts and the conflicts of this type of enterprise. For this purpose, environmental licensing processes of SHPs formalized at the Regional Environmental Regulation Superintendencies (SUPRAM) and approved by the State Council for Environmental Policy of the State of Minas Gerais in the Preliminary License phase were selected as case studies of this research. The methodology chosen is based on documental investigation, especially over the environmental studies that make up the environmental licensing processes of these enterprises, and those referring to the SUPRAM procedures for the cases considered, in order to verify how the respective processes were instructed, its coherence, uniformity and results, identifying, from there, the weaknesses of the regulatory process. The main results obtained demonstrate the low quality of the Environmental Impact Study and the Environmental Impact Report; the lack of standardization of technical analysis by the environmental agency; and the lack of capacity of the environmental agency to incorporate the participation of populations subjected to SHP’s activity impacts. Finally, based on the premise that licensing is an important instrument for assessing socialenvironmental viability in the context of the PNMA, the analysis carried out supported the proposition of a set of procedures to be considered in future analyzes of environmental licensing processes for SHPs in Minas Gerais.